Analysis of Out-Of-Plane Stability of Bow-String Arches - Josef Vican; Jaroslav Odrobinak; Jozef Gocal (Communications - Scientific letters of the University of Zilina, 2016)
Several arch bridge superstructures, designed by the authors of the paper, are presented and analysed. Spatial FEM models were utilised to analyse behaviour of each bridge. Verification of out-of-plane buckling of the arches is discussed in more detail. Comparison of using beam and shell finite elements for the mesh of main beam-arch load-carrying system is given. The variation of top bracing system and its influence on the stability of the arches is presented, as well. A minimum load amplifier to reach the elastic instability of arches is used to estimate the suitability of the bracings. Comparisons of the assessment using results produced by first and second order global analyses are presented. Application of a unique global and local imperfection as the initial geometric imperfection is proposed.